MEWUJUDKAN KEPUASAN KERJA MELALUI PENINGKATAN KOMPENSASI BAGI KARYAWAN - Rina, Rina (Pusat Penerbitan dan Publikasi Ilmiah Fakultas Ekonomi, Universitas Muslim Indonesia, 2018)
compensation is one of the implementations of HRM functions that are closely related to all types of awards that aim to increase work passion and job satisfaction. Compensation is deemed important in order to avoid negative prejudices arising from a sense of injustice between management and the labor force. This study aims to find out to analyze the relationship of compensation to Job Satisfaction. Data analysis method in this study uses regression analysis by involving all employees as many as 94 employees. The results showed that compensation had a positive and significant effect on Job Satisfaction.